IMPLEMENTASI PERATURAN DAERAH NOMOR 15 TAHUN 2011 TENTANG KAWASAN TANPA ROKOK DI KOTA PAYAKUMBUH - Ikhsan, Mhd. Rizal; Rusli, Zaili (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
No smoking area establishment was an act as protection for the people to the risk of health problems causing by the smoking act. No smoking area has to be implemented at health facility, school, playground, worship places, office, and other public places. In fact,the offenders of no smoking area was not yet gave strict punishment. This could be seen on many citizen and civil servant smoking in health facility, public places, transportation and office. The purpose of this research was to analyze implementation Non Smoking Area In Payakumbuh city and to know the influenced factors. This research using qualitative descriptive method, data collected by observation and interview where people that involved in policy implementation as informan. This research using Van Meter Van Hom theory. The results of this research shows that implementation Non Smoking Area In Payakumbuh city not totally implemented yet eventhough it already has clear standards, goals, and objectives. Human resource the monitoring of non smoking area team is inadequate because transfer and retirement of member . Coordination and communication between goverment agency running well and the execution of task fit in with the regulation. Giving warning is not carried out continuously and the enforcement of sanctions which have not been implemented ,resulting in a response as well as public participation in the regulatory environment remains low even still their public indifference towards local regulations in the region. Keyword : Implementation, cigarette ,No Smoking Area